Media multitasking as a way of personal adaptation to digital everyday life: the view of parents and teachers - G.U. Soldatova; S.V. Chigarkova; A.G. Koshevaya (Психологическая наука и образование)
Context and relevance. In the context of digital transformation of everyday life, the idea of multitasking as a necessary condition for successful activity is increasingly popular. However, there is no unambiguous position on the benefits or harms for the development of children and adolescents of multitasking and its type – media multitasking (MMT), as well as their effectiveness. Objective. The research aims to identify the attitudes of parents and teachers with varying levels of digital competence and user activity towards the phenomenon of MMT and its effectiveness. Hypothesis. Teachers and parents are characterized by more positive attitudes towards the MMT and its effectiveness in general in everyday life than in the educational context. Methods and materials. Parents and teachers (N = 283) filled out a questionnaire to assess various aspects of attitudes towards MMT, user activity, and the Digital Competence Index. Results. T While the majority of teachers and parents have a positive attitude towards MMT in everyday life, they see it as a factor that reduces the effectiveness of educational activity. Parents and teachers with higher success indicators of digital socialization are more positive about MMT. Adults who subjectively assess themselves as multitaskers are more skeptical of this format of activity, and multitasking parents do not seek to develop such activity in their children, which may be explained by its perception as a forced and resource-expensive strategy. The contradictory attitudes of adults about MMT testify to the lack of appropriate strategies for dealing with this practice in the family and at school. Conclusions. For the effectiveness of this tool, special efforts to form MMT are required. The inevitability of adolescents independently mastering MMT and their subjectively high evaluation of its effectiveness require attention from socialization institutions to provide tools for managing MMT in an adequate format without compromising children's development.